INTEGRATION OF QUR'AN INTERPRETATION AND MODERN EMBRYOLOGY: Study of Surah Al-Mu'minun Verses 12–14 - Hidayati, Fippy; Aliffa, Kurnia Nur; Candrika, Ariibah Raditya Ayu; Lutfiyah, Luthfiyah Nur (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
The phenomenon of human creation is an interesting topic to study from the perspective of religion and science. The Qur'an, contains an explicit description of the stages of fetal formation, starting from the essence of the earth, nutfah (semen), 'alaqah (a clot of blood/sticking), mudghah, the formation of bones, to the wrapping of bones with flesh and finally becoming a perfect living being. The purpose of this research is to analyze the process of fetal formation in an integrative manner through the interpretation approach and contemporary embryology science. This study uses the literature review method by examining various classical and modern textbooks, and comparing the results with scientific studies represented by embryologists such as Keith L. Moore. The results of the study show that there is a significant alignment between the sequence of fetal development according to the Qur'an and modern scientific findings. This study concludes that the integration between revelation and science not only shows the relevance of the Qur'an in the context of contemporary science, but also strengthens the understanding of the concept of i'jaz 'ilmi (scientific miracles), as well as opens up a space for constructive dialogue between science and Islamic teachings. The implication of this research is the importance of encouraging an integrative approach in Islamic education, especially in teaching kauniyah verses related to science. These findings can also be the basis for the development of a curriculum based on the integration of religion and science that is able to strengthen faith while improving students' scientific literacy.